PENGARUH KEPEMIMPINAN PEMBELAJARAN TERHADAP KINERJA MENGAJAR GURU DI SMPN SE-KECAMATAN PAMIJAHAN BOGOR - Trimulyo, Joko; Rahmawati, Ima; Khofifah, Ratu Wihdatul (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2022)
Teacher teaching performance is basically a performance that is able to plan, implement and evaluate the results of the learning process in the classroom in carrying out their professional duties. This study aims to 1) determine whether there is the effect of learning leadership on teacher teaching performanc. This research was conducted at SMPN Pamijahan sub-district, Bogor Regency. Methods of data collection using a questionnaire and interviews. The method of collecting questionnaire data was carried out on respondents by taking the sample using the Non Probability Sampling technique, using the saturated sampling method. The data analysis technique used multiple linear regression analysis. The results showed that there was a positive influence between learning leadership on teacher teaching performance. So it can be concluded that H0 is rejected and H1 is accepted.